Perancangan User Experience Situs Web Senjani Kitchen menggunakan Human Centered Design - Zainuri Mahmud; Ismiarta Aknuranda; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Senjani Kitchen is a company engaged in daily catering. In the business process Senjani Kitchen applies a coupon system. So that users are asked to buy a certain number of coupons and can use these coupons to order daily catering. However, the current process is still done manually via WhatsApp, so users must record their own coupon management. In addition, because business processes are still dependent on humans, it causes frequent errors in user orders. So that a new innovation is needed to overcome these problems. One of the innovations that can be done is with a website. In making a website, it takes a design that has a good user experience so that users will be comfortable and satisfied. Human Centered Design (HCD) is a user experience design method that focuses on user needs, so it is suitable for use as a design foundation. The results of the design evaluation that have been carried out using the User Experience Questionnaire (UEQ) get an attraction value of 1.698, a clarity value of 1.786, an efficiency value of 1.655, an accuracy value of 1.631, a stimulation value of 1.464, and a novelty value of 0.786. Where the value of attractiveness, clarity, efficiency, accuracy, and stimulation received the predicate Good, and the recency value received the predicate above average. Thus it can be concluded that the solution design has a good user experience.